Angulation toward coronal convexity measure and catheter length indication improves the quality of ventricular catheter placement: a smartphone-assisted guidance technique - Spindler, Philipp; Fiss, Ingo; Giese, Henrik; Hermann, Elvis Josef; Lemcke, Johannes; Schuhmann, Martin Ulrich; Thomale, Ulrich-Wilhelm; Schaumann, Andreas (World neurosurgery, 2022)
Background - Accurate placement of a ventricular catheter (VC) is crucial to reduce the risk of shunt failure. In the randomized, prospective, multicenter GAVCA (guided application of ventricular catheters) trial, which evaluated the quality of VC placement, the subgroup of patients with detailed length-marked VCs (dVCs) reflected a difference in the primary endpoint of optimal VC placement compared with the subgroup of patients with simplified length-marked VCs (sVCs). The objective of the present analysis was to compare the dVC and sVC groups and the smartphone-assisted guidance technique (GA) with the standard freehand technique (FH) for VC placement. - Methods - We performed a further analysis of the GAVCA trial in 2 steps. First, we compared the dVCs, which provided a detailed distance from the tip to the base (3-13 cm) in 0.5-cm intervals, with the sVCs with a length indication at 5 and 10 cm from the tip to base. Second, we compared the GA technique with the FH in the dVC group. - Results - The data from 137 patients (104 dVC patients vs. 33 sVC patients) were eligible for the present analysis. Optimal VC placement was achieved in 72.1% of the dVC group and 39.4% of the sVC group (odds ratio, 3.9; 95% confidence interval, 1.7-9.3; P ≤ 0.001). In addition, we performed a subgroup analysis of the 104 dVC patients concerning the accuracy of catheter placement using 2 different techniques (GA, n = 54; and FH, n = 50). Optimal catheter placement was achieved in 81.5% of the GA group and 62.0% of the FH group (odds ratio, 2.7; 95% confidence interval, 1.1-6.8; P = 0.03). VC placement using the GA technique was successful in all patients at the primary puncture. In contrast, for 8.7% of the patients in the FH group, multiple attempts were necessary (P = 0.03). - Conclusions - The results from the present analysis suggest that the combination of a GA technique and the use of a dVC will improve the rate of accurate VC placement. Compared with the FH technique, patient safety was increased by the reduction of unsuccessful VC placement attempts using the GA technique and dVCs.